Exploring Growth Prospects of Women Entrepreneurship in India: A Conceptual Study - Arora, Muskaan; Bedi, Aneet (Gyan Management Journal, 2019)
Entrepreneur is a person who wishes to become economically and financially independent and is also ready to accept challenges in order to meet their personal needs. Every woman has the ability to become an entrepreneur but they never gota platform to represent their forte. Although, the women in India are regarded both as source of power and also as weaker sex who is dependent on men folk Although, in India it is always discussed that both the genders are equality howeverentrepreneurship in our nation is dominated by males. However, slowly and steadily with great efforts of government, changing socio-cultural environment and an increase in educational opportunities women entrepreneurship is making remarkable change. Therefore, the Indian women needs to go a long way to get their equal rights and position as social traditions are ingrained in the Indian society. The present conceptual paper endeavors to discuss about women entrepreneurship in India-Rational for women choosing career as entrepreneurship, challenges faced by women entrepreneurs in India, Government steps taken for the upliftment women entrepreneurship and suggestions for the overall development of women.
Keywords: Entrepreneur; independent; traditions; development; India-Rational